Effect of parental consanguinity on neonatal anthropometric measurements and preterm birth in Taif, Saudi Arabia - Saied K.M. Belal; Ali K. Alzahrani; Adnan A. Alsulaimani; Amal A. Afeefy (Elsevier, 2018)
Consanguinity has received a great deal of attention as a potential risk factor of many adverse health outcomes. Consanguineous marriage is still widespread in the Middle East. The effect of consanguinity on anthropometric measurements of the newborns has been a controversial point in the past decades. The present study was carried out to assess the effects of consanguinity on various anthropometric measurements and prematurity rate among the newborns in Taif city, Saudi Arabia. A total of 1468 newborns were involved in this study after exclusion of twins, stillbirths and those with major congenital anomalies. Parental consanguinity was classified into three categories: first-cousin marriages (the baby's parents are cousins), second-cousin marriages (the baby's grandparents are cousins), and not related. The birth weight, Height and head circumference for each baby were obtained and evaluated. In addition, we assessed maternal and gestational factors known to affect the fetal growth as well as two socioeconomic indicators; maternal education and monthly income of the family. Results of the study indicated that there are no significant differences in the anthropometric measurements of the newborns between groups of different consanguinity levels. Consanguinity also showed no significant effect on the rate of preterm birth. In conclusion, it cannot be inferred that parental consanguinity has any independent effect on the anthropometric measurements or on the preterm birth rate among the newborns of our sample. Keywords: Consanguinity, Anthropometric measurements, Preterm birth, Newborns